2019
DOI: 10.1080/13683500.2019.1653831
|View full text |Cite
|
Sign up to set email alerts
|

Mountain tourism and motivation: millennial students’ seasonal preferences

Abstract: This study aimed to identify the motivations that lead a particular sub-group of the millennial generation, namely, university students, to choose mountain areas as tourism destinations both in winter and summer. Through a focus group and a questionnaire survey targeting Italian millennial students (n = 2,292), we first identified the main motivations that drive this choice. Second, we identified the level of importance for each motivation during both seasons. The findings revealed that millennials are guided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 73 publications
(143 reference statements)
1
23
0
Order By: Relevance
“…To collect data, a self-administrated questionnaire was used in this study. Before the final data collection, a preliminary survey was administrated in order to assess the clarity of the questionnaire and its suitability for the respondents (Giachino et al, 2019;Yadav and Pathak, 2016). A dozen of questionnaires were distributed to research scholars in the department in which the author works.…”
Section: Sample Characteristics and Data Collectionmentioning
confidence: 99%
“…To collect data, a self-administrated questionnaire was used in this study. Before the final data collection, a preliminary survey was administrated in order to assess the clarity of the questionnaire and its suitability for the respondents (Giachino et al, 2019;Yadav and Pathak, 2016). A dozen of questionnaires were distributed to research scholars in the department in which the author works.…”
Section: Sample Characteristics and Data Collectionmentioning
confidence: 99%
“…These tools have to comply with the needs of the environment, reinforce the cultural and social sustainability and improve the local proactivity [140][141][142]. Moreover, it is appropriate to focus on the promotion of the valley, with an offering that takes into account tourists' demands, particularly the ones of future generations [34,35], but that enhances also the territory and local productions, for example, through a local brand implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, food and wine heritage can be considered an essential resource to create appeal and support the tourism offering. Several authors indicate local food as an element of tourist attraction either in terms of consumption [29,30], heritage and territorial characterization [31][32][33], and, in some cases, it is identified as a travel motivation [34] in mountain areas [35]. Food and wine are also elements of attraction for specific population classes, significant from the point of view of consumption levels, such as the Millennials [29,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Tourism in mountain areas, after a long period of economic success and deep environmental transformation [6], has to be rediscovered [7]. The motivation stems from the importance of the attractiveness of tourism resources to tourists and plays a key role in tourism sustainability [8].…”
Section: Introductionmentioning
confidence: 99%
“…Cavagnaro et al reported that millennials demonstrate interest in themes such as natural resources and prefer destinations with significant natural resources [20][21][22][23][24][25]. Giachino et al [7] found seasonal differences in the millennials' choice of nature tourism destinations. Tieskens et al [26,27] demonstrated that analytical studies on elements of mountain cultural landscapes are of high research value in exploring tourists' preferences for mountain landscapes.…”
Section: Introductionmentioning
confidence: 99%